Co-exposure to deoxynivalenol and hexavalent chromium is associated with intestinal injury, dysbiosis, and activation of ferroptosis and pyroptosis related pathways in broilers - Yueming Gu; Xinyuan Miao; Linrui Fan; Guodong Cai; Ruilong Song; Hui Zou; Jianhong Gu; Yan Yuan; Xuezhong Liu; Zongping Liu; Jianchun Bian (Food Research International, 2026)

ALN-modified MnO2-x/PEEK implant for bone-targeted catalytic therapy in postoperative osteosarcoma repair - Miaomiao He; Ce Zhu; Dan Sun; Yueming Song; Ganjun Feng; Limin Liu; Li Zhang (Chemical Engineering Journal, 2025)

Porous spherical g-C3N4/geopolymer composite for photo-Fenton-like degradation of tetracycline hydrochloride - Yutong Song; Xiaohong Zhang; Chengying Bai; Wei Peng; Yueming Ren; Xiaodong Wang; Ting Zheng; Paolo Colombo; Bin Wang (Journal of Water Process Engineering, 2025)

Understanding the anti-browning mechanism and physicochemical properties in potato pulp during the magnetic field processing - Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Xin Zhang; Chuangshuo Yan; Yujian Xie; Dongliang Zhang; Hongjun Li (Food Chemistry, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Progress in Preparation Technology and Functional Research On Marine Bioactive Peptides - Jing Wang; Fengcheng Li; Wenjun Li; Yueming Li; Jian Zhang; Song Qin (Marine Biotechnology, 2025)

Multi-objective optimization based on the RSM-MOPSO-GA algorithm and synergistic enhancement mechanism of high-performance porous concrete - Guanglei Qu; Mulian Zheng; Chuan Lu; Jiakang Song; Dazhi Dong; Yueming Yuan (Journal of Cleaner Production, 2025)

Multifunctional neuroimmunoregulatory nanoenzyme-enhanced hydrogel promotes bone regeneration by improving bone healing microenvironment - Qiujiang Li; Xingxia Long; Linnan Wang; Xi Yang; Huiliang Yang; Bowen Hu; Ce Zhu; Zhuang Zhang; Zhipeng Deng; Junhu Li; Shuxin Zheng; Lei Wang; et al. (Chemical Engineering Journal, 2025)

Disentangling the effects of meteorology and emissions from anthropogenic and biogenic sources on the increased surface ozone in Eastern China - Min Shao; Shun Lv; Yueming Song; Rui Liu; Qili Dai (Atmospheric Research, 2024)

Structural insight into the dual-antagonistic mechanism of AB928 on adenosine A2 receptors - Yuan Weng; Xinyu Yang; Qiansen Zhang; Ying Chen; Yueming Xu; Chenyu Zhu; Qiong Xie; Yonghui Wang; Huaiyu Yang; Mingyao Liu; Weiqiang Lu; Gaojie Song (Science China Life Sciences, 2024)

Understanding the degradation mechanisms of cyanide and starch in cassava flour during extrusion processing - Mingming Qi; Jialin Song; Lijun Jiang; Luxia Li; Mei Xu; Yueming Li; Shifeng Yu; Hongjun Li (Innovative Food Science & Emerging Technologies, 2024)

Source Apportionment of Soil Heavy Metal(Loid)s in Farmland Using Diverse Models: A Comparative Assessment in the Yellow River Delta - Wei Huang; Shuhuan Wang; Lu Wang; Yingqiang Song; Yue Zhu; Hao Yang; Yingkai Xie; Yueming Hu (Journal of Marine Science and Engineering, 2023)
The rapid development of industrialization and urbanization has posed serious challenges for coastal farmland ecosystems. Source apportionment of soil heavy metals is an effective way for the detection of non-point source pollution in farmland to help support the high-quality development of coastal agriculture. To this end, 113 surface soil samples were collected in the coastal delta of China, and the contents of As, Cd, Cr, Cu, Ni, Pb, and Zn were determined. A variety of models were integrated to apportion the source of soil heavy metals, including positive matrix factorization (PMF), geographical detector (GD), eXtreme gradient boosting (XGBoost), and structural equation modeling (SEM). The result of PMF models revealed that there was collinearity between various heavy metals, and the same heavy metal may have a mixed source. The XGBoost model analysis indicated that there were significant non-linear relationships between soil heavy metals and source factors. A synergy between air quality and human activity factors was the key source of heavy metal that entered the study area, based on the results of the GD. Furthermore, the input path effect of heavy metals in the soil of the study area was quantified by SEM. The balance of evidence from the above models showed that air quality (SO2 and NO2) and factories in the study area had the greatest impacts on Cd, Cr, and Zn. Natural sources were dominant for Pb, while As, Cu, and Ni were contributed by soil parent material and factories. The above results led to the conclusion that there was a cycle path in the study area that continuously promoted the migration and accumulation of heavy metals in farmland soil; that is, the heavy metals discharged during oil exploitation and smelting entered the atmosphere and then accumulated in the farmland soil through precipitation, atmospheric deposition, and other paths. In this study, it is shown that a variety of models can be used to more comprehensively assess the sources of soil heavy metals. This approach can provide effective support for the rapid prevention and decision-making management of soil heavy metal pollution in coastal areas.

Integration of metabolomics and proteomics analysis to explore the mechanism of neurotoxicity induced by receipt of isoniazid and rifampicin in mice - Xiaoyu Qu; Jie Ma; Huan Gao; Yueming Zhang; Jinghui Zhai; Jiawei Gong; Yanqing Song; Tingting Hu (NeuroToxicology, 2023)

Treatment of cauda equina syndrome caused by lumbar disc herniation with percutaneous endoscopic lumbar discectomy - Xiaolong Li; Qingyu Dou; Shuai Hu; Jiaxiang Liu; Qingquan Kong; Jiancheng Zeng; Yueming Song (Acta Neurologica Belgica, 2016)

Paleogene-Neogene stratigraphic realm and sedimentary sequence of the Qinghai-Tibet Plateau and their response to uplift of the plateau - KeXin Zhang; GuoCan Wang; JunLiang Ji; ManSheng Luo; XiaoHu Kou; YueMing Wang; YaDong Xu; FenNing Chen; RuiMing Chen; BoWen Song; JianYu Zhang; YinPing Liang (Science China Earth Sciences, 2010)